The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1002/jum.14320
|View full text |Cite
|
Sign up to set email alerts
|

Left Ventricular Septal Hypertrophy in Elderly Patients With Aortic Stenosis

Abstract: Objectives-Left ventricular (LV) septal hypertrophy in aortic stenosis raises diagnostic and therapeutic questions. However, the etiology and clinical consequences of this finding have not been well studied. The aim of this study was to perform a morphologic evaluation of the LV in aortic stenosis and to investigate the contributing factors and consequences of septal hypertrophy.Methods-Patients with moderate or severe aortic stenosis were prospectively enrolled. Patients with previous myocardial infarction, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
5

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 28 publications
0
4
0
5
Order By: Relevance
“…This phenotype, which shows a pattern more characteristic of cardiac dysfunction than of non-asymmetrical hypertrophy, resembles that in patients with hypertrophic cardiomyopathy ( Marian and Braunwald, 2017 ; Yousefzai et al, 2017 ), one of the leading causes of sudden death among young people ( Maron and Maron, 2013 ). Although it has been shown that hypertrophic cardiomyopathy may be inherited ( Katayama et al, 2018 ), it seems unlikely that the effects observed in our global KO model are early development related, since basal signs of cardiac hypertrophy do not develop spontaneously in young Metrnβ-null mice. However, we cannot completely rule out this possibility, because Metrnβ has been reported to have effects on neuronal growth and brain development during embryogenesis ( Jørgensen et al, 2012 ).…”
Section: Discussionmentioning
confidence: 83%
“…This phenotype, which shows a pattern more characteristic of cardiac dysfunction than of non-asymmetrical hypertrophy, resembles that in patients with hypertrophic cardiomyopathy ( Marian and Braunwald, 2017 ; Yousefzai et al, 2017 ), one of the leading causes of sudden death among young people ( Maron and Maron, 2013 ). Although it has been shown that hypertrophic cardiomyopathy may be inherited ( Katayama et al, 2018 ), it seems unlikely that the effects observed in our global KO model are early development related, since basal signs of cardiac hypertrophy do not develop spontaneously in young Metrnβ-null mice. However, we cannot completely rule out this possibility, because Metrnβ has been reported to have effects on neuronal growth and brain development during embryogenesis ( Jørgensen et al, 2012 ).…”
Section: Discussionmentioning
confidence: 83%
“…We retrieved a total of 7 247 902 drug-event pairs between January cardiomyopathy. 26,27 Myocardial fibrosis is a significant risk factor for hypertrophic cardiomyopathy, and is associated with a myriad of severe adverse cardiovascular outcomes including sudden cardiac death, ventricular tachyarrhythmias, left ventricular dysfunction, and heart failure. 28…”
Section: Resultsmentioning
confidence: 99%
“…However, our novel findings include the identification of cardiac septal hypertrophy and myocardial fibrosis associated with hydroxychloroquine therapy, and these signals require further confirmation. Cardiac septal hypertrophy in older adults is associated with disturbance in intraventricular conduction and is an independent predictor of progression to atrial fibrillation in patients with hypertrophic cardiomyopathy 26,27 . Myocardial fibrosis is a significant risk factor for hypertrophic cardiomyopathy, and is associated with a myriad of severe adverse cardiovascular outcomes including sudden cardiac death, ventricular tachyarrhythmias, left ventricular dysfunction, and heart failure 28 …”
Section: Discussionmentioning
confidence: 99%
“…Несмотря на значимые достижения активного полувекового изучения этой загадочной патологии сердца, многочисленные современные научные исследования продолжают предпринимать попытки эволюционировать представление о ГКМП с целью определения парадигм диагностики и лечения. Подобная актуальность связана с тем, что на фоне постепенно нарастающей одышки, основным проявлением ГКМП является внезапная сердечная смерть (ВСС) [1]. Гипертрофическая кардиомиопатия, как причина ВСС у молодых людей, является наиболее часто встречающейся, а у действующих спортсменов занимает первое место среди прочих сердечно-сосудистых патологий, достигая 36% [2, 3,4].…”
Section: гипертрофическая кардиомиопатия -современное состояние много...unclassified